Georgia : Joint Staff Assessment of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2003)
The Economic Development and Poverty Reduction Program of Georgia (EDPRP) is the first full poverty reduction strategy paper (PRSP) prepared by the government. The PRSP presents two macroeconomic scenarios, a realistic one and an optimistic one. The presentation of fiscal policy objectives in the EDPRP suffers from lack of specificity on the main components of future tax reform. IMF staff has advised strongly against the EDPRP proposal to set up a special Poverty Alleviation Fund within the regular state budget. The participation and communication program is thorough and detailed.